Modification of POSS and their tribological properties and resistant to space atomic oxygen irradiation as lubricant additive of multialkylated cyclopentanes - Wang, Xingwei; Zhang, Chaoyang; Zhao, Chen; Liang, Yijing; Zhang, Ming; Yang, Wufang; Yu, Bo; Yu, Qiangliang; Cai, Meirong; Zhou, Feng; Liu, Weimin (Friction, 2024)
Developing functional additive resistant to space atomic oxygen (AO) irradiation through simple molecular design and chemical synthesis to enhance the lubricating performance of multialkylated cyclopentanes (MACs) oil is a significant challenge. Herein, sulfur-containing polyhedral oligomere silsesquioxane (POSS) were synthesize via a click-chemistry reaction of octavinyl polyhedral oligomeric with alkyl sulfide. The reduce-friction (RF), anti-wear (AW) properties and anti-AO irradiation of POSS-S-R as MACs base oil additives in atmospheric and simulated space environments were systematically investigated for the first time. Results demonstrate that POSS-S-R not only possesses outstanding anti-AO irradiation capacity but also effectively improves the RF and AW of MACs in atmospheric or simulated space surroundings. This improvement is due to the excellent anti-AO irradiation properties of the POSS structure itself and the high load-carrying ability of silicon-containing and sulfur-containing compounds generated by tribo-chemical reactions, which effectively separates the direct contact of the friction interface. We believe that this synthesized POSS-S-R is a promising additive for space lubricants.